Critical factors for generation Z intention to pursue higher education - Liew, Ying Ying (2023)
The purpose of this empirical study is to investigate the friends and peer influence, financial aid, motivation, self-efficacy, family influence and intention to pursue higher education among Generation Z. The research is conducted to study the Critical Factors For Generation Z Intention to Pursue Higher Education in Malaysia. In this research, questionnaires were adapted and the data of 425 respondents have been collected. Data analysis was done by using SPSS software. After the collection of data, Cronbach’s Alpha Reliability test was conducted to test the reliability on each variable. Pearson Correlation Coefficient and Multiple Linear Regression Analysis are used to examine the relationship between independent variables and dependent variables. The three independent variables showed a significant relationship on students‟ intention to pursue higher education.